Dimensi Spiritualitas dalam Pola Asuh Anak: Analisis Integratif Perspektif Psikologi dan Teologi Alkitabiah - Eunike Irene Alicia; Kornelius Rulli Jonathans; Haryadi Sarjono (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
The crisis of spiritual role-modeling and the phenomenon of spiritual neglect in the modern era trigger a stagnation in children's spirituality, a condition exacerbated by the scarcity of integrative literature synthesizing developmental psychology and theology. This qualitative study utilizes a library research approach to construct a comprehensive child-rearing model through an integrative analysis of psychological perspectives and Biblical theology. The findings demonstrate that children’s spirituality evolves through cognitive, emotional, and relational consciousness maturity, which is reinforced by the theological mandate of the Shema in Deuteronomy 6:6–7. The synthesis of these two disciplines yields a spirituality-based parenting model built upon three core pillars: first, repositioning parents as spiritual mentors through an authoritative-egalitarian parenting style. Second optimizing the family as the epicenter of spiritual formation. And third, internalizing values that manifest in everyday praxis. This model offers a transformative solution for parents and church educators to guide children holistically amidst the disruptions of the digital age. Abstrak Krisis keteladanan rohani dan fenomena spiritual neglect di era modern memicu stagnasi spiritualitas anak, yang diperparah oleh keterbatasan literatur integratif antara psikologi perkembangan dan teologi. Penelitian kualitatif dengan pendekatan studi kepustakaan ini bertujuan untuk mengonstruksi model pengasuhan anak yang komprehensif melalui analisis integratif antara perspektif psikologi dan teologi Alkitabiah. Hasil kajian menunjukkan bahwa spiritualitas anak berkembang melalui kematangan kognitif, emosional, dan relational consciousness, yang diperkuat oleh mandat teologis Shema dalam Ulangan 6:6-7. Sintesis kedua disiplin ilmu ini menghasilkan model spirituality-based parenting dengan tiga pilar. Pertama, reposisi orang tua sebagai mentor spiritual melalui pola asuh otoritatif-egaliter. Kedua, optimalisasi keluarga sebagai episentrum formasi spiritual. Dan ketiga, internalisasi nilai yang mengejawantah dalam praksis kehidupan sehari-hari. Model ini menawarkan solusi solutif bagi orang tua dan pendidik gerejawi dalam membimbing anak menghadapi disrupsi era digital secara holistik.